Comparative analysis of electroneuromyographic values in patients with scapulohumeral pain syndrome of degenerative genesis and cervical osteochondrosis - E. G. Ippolitova; T. K. Verkhozina; N. I. Arsentieva (Acta Biomedica Scientifica, 2016)
The aim of the research was to study electrophysiological values in patients with blade-humerus pain syndrome at cervical osteochondrosis and posttraumatic shoulder injuries. We managed 71 patients: 33 patients with cervical osteochondrosis and brachialgia getting conservative treatment in the neurosurgical unit of Irkutsk Scientific Center of Surgery and Traumatology (group 1) and 38 patients with injuries of shoulder joint capsules and ligaments getting treatment in the unit of traumatology and orthopedics (group 2). Comparison of electroneuromyographic values in patients of both groups showed unidirectional changes in the values and accentuated decrease in electroneuromyographic parameters on both affected and unaffected extremities. In both cases median nerve was affected most. We registered the decrease in conduction velocity of motor fibers of intact nerves in patients of both groups. Lack of clinical signs of lesion of these nerves can be indicative of functional changes in nerve conduction which reflect generalized reaction on the lesion of certain nerve stems.